Smart Farming Revolution: AI, IoT, and Robotics in Precision Agriculture and Soil Conservation - Bhaba Krishna Kuli; Joytu Debnath; Asaruddin Sheikh; Samiran Das; Pritam Singh Balai (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Advances in artificial intelligence (AI), the internet of things (IoT), and robotics are reshaping how precision agriculture is practiced and how soil resources are preserved. The technologies allow for decision-making based on data, resource optimization, and environmentally friendly farming. AI allows for sophisticated predictive analysis, which means farmers can predict yield results, detect diseases in advance, and maximize planting timetables. IoT-based sensor networks enable real-time soil health monitoring, weather patterns, and crop development, enabling more efficient and timely farm operations. Robotics transforms conventional farm work by bringing autonomous platforms to seeding, harvesting, and soil testing, lowering labor costs and improving operational effectiveness. By better management of water, reduced land erosion, and reduced wastage of fertiliser, the use of such intelligent technologies not only enhances the productivity of agriculture but also ensures the conservation of soil. Robotic automation, IoT-based monitoring systems, and AI-based analytics play an important role in enhancing agricultural productivity and environmental sustainability, which is emphasized in the discussion of existing trends in intelligent agriculture in this paper.
Keywords: Smart Farming; Artificial Intelligence (AI); Internet of Things (IoT); Agricultural Robotics; Smart Irrigation Systems; 5G Connectivity